Free Radical Scavenger Activity of Cinnamyl Chitosan Schiff Base - T M Tamer & , Katarina Valachová, Mohamed Samir Mohyeldin, Ladislav Soltes (Journal of Applied Pharmaceutical Science, 2016)
In this study, new cinnamyl chitosan schiff base was evaluated as antioxidant material. Antioxidant activity was measured by two different popular methods (uninhibited/inhibited hyaluronan degradation and decolorization of ABTS methods). the results show decrease the hydrogen donation behavior of chitosan after coupling with cinnamaldehyde, in the other hand, ABTS method show increase the electron donation activity of cinnamyl chitosan than the chitosan itself.
Keywords: Chitosan,Cinnamyl chitosan,Schiff base,Antioxidant,Rotational viscometer,ABTS,Hyaluronan.